The Future Of The Shariah And The Shariah Courts In Malaysia - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 1993)
Before the coming of the Colonial powers, the law which was applied in the Malay States was the Islamic law, which had absorbed to some extent the rules of the Malay custom.